Everyday coaching : using conversation to strengthen your culture - Bianco-Mathis, Virginia; Nabors, Lisa K. (ATD Press, 2017)
Unleash Hidden Potential With Coaching Conversations. Coaching is not just for coaches. When everybody within an organization learns and develops coaching skills, its culture begins to change. The exchange of meaningful and actionable feedback becomes the norm and not something that only occurs during annual performance appraisals. The willingness to share insights and ideas becomes accepted and expected at all levels--up, down, and across. Virginia Bianco-Mathis and Lisa Nabors believe everyone in an organization can master a new language--dialogue--and use it in the service of excellence and continuous learning. Everyday Coaching endorses the idea that by improving coaching dialogue skills, people will show up, every day, knowing that what they say and do makes a difference. Through practical tips and examples, Everyday Coaching demonstrates the difference between conversations and true dialogue: the power of using the language of coaching to achieve expectations, personal growth, and overall strategic success. With an easy-to-use coaching model, you can practice formally or informally giving feedback, making agreements, and guiding behavior. In this book, you'll learn to: · Use coaching to create a culture of collaboration. · Inspire meetings and agendas with more purposeful conversations. · Embody coaching as a normal way of going about continuous improvement. Not everyone is a professional coach. But with Everyday Coaching everyone can take the best of what coaching has to offer--the dialogue, tools, and mindset--and leverage it to transform themselves and their organization.